Study on Improving MSMEs Performance through Business Strategies - Esa Dilla Maulani; Yudha Trishananto; Ulfah Nurul Fauziah (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of the independent variable innovation on the performance of SMEs in Salatiga City with the business strategy variable as an intervening. This study is a quantitative study using primary data from a population of all MSME owners in Salatiga in 2022. This study emphasizes resource-based theory (RBT) which emphasizes competitive advantage in companies. The sampling technique used is simple random sampling, which produces 100 samples. Data collection methods were carried out using questionnaires and interviews with MSME owners in the city of Salatiga in 2022. The data was processed using the IBM SPSS statistic version 23. The results in this study indicate that innovation and business strategy have a positive and significant effect on MSME performance, innovation has a positive effect and significant impact on business strategy, and finally, the business strategy succeeded in mediating innovation on the performance of MSMEs.